Arene Complexes of Divalent Tin Bromoaluminates. Issue 21 (3rd March 2017) - Schleep, Mario; Ludwig, Thilo; Hettich, Clarissa; Leone, Selina; Krossing, Ingo
Abstract : Numerous arene complexes of tin(II) are well known with [AlCl4 ] – as counterion, but none with the analogous [AlBr4 ] – ion. Herein we report on new crystal structures containing arene complexes of tin and the tetrabromoaluminate anion obtained out of the reactions between SnBr2 and AlBr3 in the respective arene as solvent. Additionally, powder diffraction data and FIR spectra of the bulk products of these reactions are discussed. Abstract :